Collaboration between investigation and crisis intervention for the investigative interview in suicide attempts - Gönültaş, Burak M. (Varstvoslovje, 2020)
Purpose: The present study aims to understand whether investigation and crisis intervention processes can be coupled together in suicide attempt cases in order to mitigate secondary victimisation and whether a social worker as an interventionist can accomplish this. Design/Methods/Approach: This study relies on a literature review with the help of various databases, including PubMed, Springer Database, PsycoINFO and official national and international websites. In this study, the keywords (suicide, crisis intervention, investigation, social work, social worker) were determined for screening according to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Findings: We found 38 articles, 8 of which were categorised by the research team in several groups with a level of 92% agreement. We categorised them using the mentioned keywords and four groups emerged as a result: suicide and crisis intervention, crisis intervention and social workers, suicide and investigation, investigation and social work. Overviews of papers for each group are presented. Practical Implications: Investigative interviews and crisis intervention processes may be coupled together in cases of suicide attempts. This process holds the potential to increase the rigour and effectiveness of data collection for the case, allow experts to lend their knowledge and skills in support of each other, and provide opportunities for more comprehensive problem-solving in crises. Thus, according to the literature and practice, the output of the current study appears to be implementable. Originality/Value: The conceptual framework revealed in this study may be used as a valuable source for future studies on the topic of collaboration occurring between the investigation on one side and social and psychological crisis intervention services on the other.
Keywords: crisis intervention; investigative interviewing; krizna intervencija; police; policija; preiskovalni intervju; samomor; social worker; socialni delavec; suicide